Contesting victim narratives: Indian women domestic workers in Oman†. (2nd September 2017) - Mehta, Sandhya Rao
Abstract : This paper focuses on Indian migrant workers in Oman, with particular emphasis on women in the non-formal, domestic sector. Drawing on studies on gender and mobility, it argues for an intersectional approach to gendered migration which centres the narrative on migrant women themselves, given the layered and complex strategies adopted by them to confront their migrant situation. Based on a decade long personal interaction and personal interviews with 15 Indian female domestic workers in Oman, this study attempts to problematise established binaries of victimhood, exploitation and protection by focusing on the multiple ways in which women cope and wrest autonomy within a patriarchal system of both, the sending and receiving countries, thus facilitating a layered and heterogeneous approach to the experience of women's migration in the Gulf Cooperation Council countries, especially in the way they negotiate through the kafala system of sponsorship which is particular to this region.